Szafa marzeń. Dziecięce kryjówki w E.T. Stevena Spielberga - Kostyra, Karolina (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The filmmakers made efforts to present reality from a child’s viewpoint. Among the strategies applied for this purpose, we find a detailed approach to grasping the atmosphere of children’s bedrooms. The wardrobe, intimate lighting, cozy nooks and child’s props allow the creation of a space of autonomy and the uncanny effect, which slips away from adults’ perception. The author uses works on the anthropology of place, the psychoanalysis of dreams, film studies analyses of E.T. and also the history of cinematic representation of children’s worlds in order to describe the specificity of domestic space in Spielberg’s movie. At the same time, the author proposes that E.T. can be interpreted as a movie about the relative independence of children’s worlds in relation to the overpowering and stifling American suburbs. If we follow the proposed interpretation, then the popular judgment of E.T. as a conservative and family narration from Reagan’s days would seem to be too one-sided.